The Influence of Product Quality and Price on Samsung Smartphone Customer Satisfaction: Case Study on Students of The Faculty of Economics, Makassar State University - Sri Sandro, Nandi Rasdina (PT. Maju Malaqbi Makkarana, 2023)
This study is a quantitative study that aims to determine the effect of product quality and price on consumer satisfaction of Samsung smartphones (a case study on students of the Faculty of Economics, State University of Makassar). The independent variables in this study are product quality and price, while the dependent variable is consumer satisfaction. The population in this study were all active students of the Faculty of Economics, State University of Makassar class of 2018, using the Sampling method, a sample of 100 respondents was obtained. Data collection techniques used are questionnaires, literature study, and documentation. The data analysis technique used is multiple linear regression analysis using Statistical Product and Service Solution (SPSS) v. 13. The results of this study indicate that product quality (X1) partially has a significant effect on consumer satisfaction for Samsung smartphones. Price (X2) partially has a significant effect on consumer satisfaction of Samsung smartphones. And product quality (X1) and price (X2) simultaneously have a significant effect on consumer satisfaction for Samsung smartphones.